2006
DOI: 10.1295/polymj.pj2005208
|View full text |Cite
|
Sign up to set email alerts
|

Non-Polar Polymer Nanotubes and Nanowires Fabricated by Wetting Anodic Aluminium Oxide Template

Abstract: ABSTRACT:Non-polar polymer nanotubes and nanowires were fabricated using nanoporous Anodic Aluminium Oxide (AAO) template via a physical wetting of the polymer solution and melt. Testing results of field emission scanning electron microscopy (FESEM) demonstrate that non-polar polymer nanotubes can be prepared by polymer solution, while nanotubes and nanowires can be obtained by polymer melt at higher temperature and at lower temperature respectively. As for melt wetting method, there is a critical temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…She et al observed that wetting AAO membranes having a D p -value of 200 nm with polyamide 66 at 250 • C yielded nanowires [68]. Similar results were obtained for poly(propylene) [69]. Correspondingly, at a given infiltration temperature and for a given polymer, precursor wetting will occur if the molecular weight of the polymer is relatively low, whereas capillary wetting will occur in the case of relatively high molecular weights.…”
Section: Capillary Wetting Of Porous Templatesmentioning
confidence: 71%
See 2 more Smart Citations
“…She et al observed that wetting AAO membranes having a D p -value of 200 nm with polyamide 66 at 250 • C yielded nanowires [68]. Similar results were obtained for poly(propylene) [69]. Correspondingly, at a given infiltration temperature and for a given polymer, precursor wetting will occur if the molecular weight of the polymer is relatively low, whereas capillary wetting will occur in the case of relatively high molecular weights.…”
Section: Capillary Wetting Of Porous Templatesmentioning
confidence: 71%
“…When the diameter of the pores in the hard template is reduced below about twice the radius of gyration of the infiltrated polymeric species, the hollow space in the tubes disappears and solid rods are obtained [64][65][66][67]. In general, precursor wetting takes place if the pore walls of the hard template exhibit high surface energy and if the polymeric melts are heated to temperatures well above their glass transition temperature [61,68,69]. However, many aspects of precursor wetting still need to be elucidated.…”
Section: Precursor Wetting Of Porous Templates With Polymeric Meltsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The obtained PA66 nanotubes enveloped into AAO can be used as a ''secondary template'', into which the metal nanowires are prepared by electrochemical deposition. The polymer/metal nanocables are formed at last.…”
Section: -21mentioning
confidence: 99%
“…In the literature, one can find a description of the use of this technique for manufacturing nanomaterials of conductive [12,13], ferroelectric [14], elastic [15], semiconducting [16], nonpolar [17], and dielectric polymers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%